ДИСФУНКЦИЯ ЯИЧНИКОВ И СУБИНВОЛЮЦИЯ ПРОДУКТИВНЫХ КОРОВ И БЕСПЛОДИЯ В ПОСЛЕДСТВИЕ ИХ (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Anatation: The article describes the causes of uterine subinvolution, ovarian hypofunction and associated infertility in productive cows, developmental features, clinical and hemomorphobiochemical changes, and analysis of the results obtained.